2016
DOI: 10.1186/s13014-016-0646-2
|View full text |Cite
|
Sign up to set email alerts
|

Integration of 68Ga-PSMA-PET imaging in planning of primary definitive radiotherapy in prostate cancer: a retrospective study

Abstract: BackgroundProstate cancer (PC) is one of the most commonly treated cancer entities with radiation therapy (RT). Risk group-adapted treatment and avoidance of unnecessary toxicities relies primarily on accurate tumor staging. Thus, the introduction of prostate-specific membrane antigen (PSMA) in diagnosis and treatment of PC is a highly interesting development in radiation oncology of urologic tumors. The present work is to evaluate the integration of 68Ga-PSMA-PET imaging into standard radiation planning of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 23 publications
1
56
3
2
Order By: Relevance
“…Morigi et al prospectively evaluated the impact on management of 68 Ga-PSMA-11 in patients with BCR and prior 18 F-fluorocholine treatment; they demonstrated a major impact in approximately one-third of patients, especially those with a low PSA level (78). Two other studies reported similar results (91,92). Data are limited in patients with metastatic disease.…”
Section: Psma Ligand Imaging Biochemical Recurrencementioning
confidence: 99%
“…Morigi et al prospectively evaluated the impact on management of 68 Ga-PSMA-11 in patients with BCR and prior 18 F-fluorocholine treatment; they demonstrated a major impact in approximately one-third of patients, especially those with a low PSA level (78). Two other studies reported similar results (91,92). Data are limited in patients with metastatic disease.…”
Section: Psma Ligand Imaging Biochemical Recurrencementioning
confidence: 99%
“…Several studies have investigated the impact of PSMA ligand PET/CT on patient management and therapy. Most studies have focused on the value of PSMA ligand PET/CT in patients with BCR after curative treatment and have reported changes in therapeutic management depending on the specific clinical scenario and the extent of treatment modification (69)(70)(71)(72)(73)(74). Most recently, an overall change in the therapeutic management of 75% of 131 patients after primary treatment was shown (69).…”
Section: Impact On Treatment Planningmentioning
confidence: 99%
“…In a well-defined patient cohort before salvage radiotherapy, a major management change in 20 of 70 patients (28.6%) with a PSA level of less than 1 ng/mL was demonstrated by van Leeuwen et al (74). In the setting of primary treatment, a small cohort of 15 patients underwent PSMA ligand PET/CT, and the imaging was found to influence clinical TNM stage in 53.3% of patients and radiotherapy plan in 33.3% (71). Combining the settings of radiotherapy planning in both primary and recurrent disease, 2 recent publications reported PSMA ligand PET/CT to have an impact on 50.8% and 53.7% of patients (72,73).…”
Section: Impact On Treatment Planningmentioning
confidence: 99%
“…A recently published meta-analysis summarized the available studies and reported in patients with BCR an overall positivity rate of 76 % [27]. However, only limited data are available regarding the impact of 68 Ga-PSMA PET/CT on SRT planning [2830]. Change of treatment based on the 68 Ga-PSMA PET/CT findings has been reported in 50.8 and 53.7 % of patients, but these cohorts included primary disease and BCR [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Change of treatment based on the 68 Ga-PSMA PET/CT findings has been reported in 50.8 and 53.7 % of patients, but these cohorts included primary disease and BCR [29, 30]. Dewes et al found a change of TNM stage in 53.3 % and a change in RT concept in 33.3 % of cases prior to initial curative RT [28]. Patient cohorts were heterogeneous, and only very limited data are available on patient outcome in 68 Ga-PSMA PET/CT-guided RT [31].…”
Section: Introductionmentioning
confidence: 99%